Semen extender triggers a mild physiological inflammatory response in the uterus without disrupting sperm-uterine immune crosstalk in vitro in cattle - Malinda HULUGALLA; Alireza MANSOURI; Elham WAEHAMA; Ihshan AKTHAR; Akio MIYAMOTO (The Journal of Reproduction and Development)
Artificial insemination (AI) in cattle involves introducing frozen-thawed sperm, a minimal amount of seminal plasma, and a significant volume of semen extender (SE) into the uterus. Previous studies have demonstrated that sperm interact with bovine endometrial epithelia via TLR 2/1, triggering a weak inflammatory response to clear the endometrium. This study investigated the impact of the major component of the insemination dose, egg yolk-based SE, on the uterine immune response in vitro. The results showed that SE did not affect sperm kinetic parameters or the entry of sperm into the uterine glands. SE alone significantly upregulated the mRNA expression of inflammatory cytokines (NFKB2, TNF, IL1B, CXCL8), TLR2/1, and the inflammasome NLRP3, while downregulating NOD1. Immunofluorescence analyses confirmed the upregulation of the strong inflammatory marker TNF alongside TLR2 and the downregulation of NOD1 in the uterine epithelium, similar to the effects observed with sperm. When combined with sperm, SE did not enhance the protein or mRNA expression of these markers, except for IL1B and CXCL8. In silico analyses revealed a strong affinity between triglycerides (the primary components of egg yolk) and TLR2/1, suggesting a potential role in stabilizing heterodimerization. These findings demonstrate that egg yolk-based SE, independent of sperm, triggers a mild physiological inflammatory response mediated by the TLR2/1 and NOD1 signaling pathways. The suppression of NOD1 by sperm and SE ensures a controlled and weak immune response in the uterus. Notably, despite the SE-induced inflammation, the sperm-uterine immune crosstalk was not disrupted, suggesting that SE does not negatively impact the physiological interactions between sperm and the uterus during AI.